Q: What is the property 53x plus 4 equals 15x plus 20?

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

It equals 53X- a number is squared when it is multiplied by itself, so 7X by 7X = 49X. 2X by 2X =4X, so 49X + 4X is 53X.

Assuming the missing number as XX + 53 = 180X = 180 - 53X = 127127 is the Answer

9x-53=6/x 9x2-53x=6 9x2-53x-6=0 9x2+x-54x-6=0 x(9x+1)-6(9x+1)=0 (9x+1)x(x-6)=0 9x+1=0 or x-6=0 9x=-1 or x=6 x=-1/9 or x=6

5- s 3-e X- x I had to figure it out myself 'cause my friend forced me too.... I hope u don't get scarred for like dude/dudette :|

I assume there are a missing + and =, that is the equation is either:3x + 5y = 53x = 5y + 5(though the first is the most likely).They are both the equation of a straight line.

Related questions

55x + (-3) = 53x + 7can be written as55x - 3 = 53x + 7subtract 53x from both sides2x - 3 = 7add three to both sides2x = 10divided both sides by 2x = 5

3x-1+10 = 53x + 9 = 53x = 5 - 93x = -4x = -4/3

It equals 53X- a number is squared when it is multiplied by itself, so 7X by 7X = 49X. 2X by 2X =4X, so 49X + 4X is 53X.

53x =15 : x = 53/15 = 3.5333 (4dp)

53x or 5.3 by 10x or 530 by 0.1x

It's not something that can have a SOLUTION unless it EQUALS something. x + 53x = 54x. Does 54x = 1? Then x = 1/54. Does 54x = 108? Then x = 2. etc.

Assuming the missing number as XX + 53 = 180X = 180 - 53X = 127127 is the Answer

3X + 5 = 23subtract 5 from each side3X + 5 - 5 = 23 - 53X = 18divide both sides integers by 3(3/3)X = 18/3X = 6=======check by inserting 6 where X is in original equation3(6) + 5 = 2318 + 5 = 2323 = 23========checks

9x-53=6/x 9x2-53x=6 9x2-53x-6=0 9x2+x-54x-6=0 x(9x+1)-6(9x+1)=0 (9x+1)x(x-6)=0 9x+1=0 or x-6=0 9x=-1 or x=6 x=-1/9 or x=6

Point of passage (6, 2) and a slope of 53 Equation: y-2 = 53(x-6) => y = 53x-316

HaHa ofcourse it does who wouldn't get HORN3Y

Please restate your question, but use () and < in it, so that it will make more sense. Then it will be easier to answer. I assume you mean: 1 - 5(3x) < 2(x - 5) - 7x. (If it were 1 - (53x) < 2(x - 5) - 7x, there would have been no need for the first parentheses.) The first thing you would do is distribute both the 5 and the 2: 1 - 15x < 2x - 10 - 7x Combine like terms: 1 - 15x < -5x -10 Get rid of one of the x terms. We will get rid of the -15x by adding 15x to both sides. (Whatever you do to one side, you have to do to the equivalent to the other, and I will choose which one to get rid of by choosing the one that causes me to end up with a positive x term, if possible.) 1 < 10x - 10 Now we will get rid of the -10 by adding 10 to both sides. 11 < 10x Divide both sides by 10: 11/10 < x Flip the equation around (including the sign) so that the x term is on the left: x > 11/10.